Sugar and GATT : the challenge continues. - HARAKSINGH, Kusha (1995)
Focuses on the GATT negotiations with regard to sugar. Argues that the region has to search for the creative potential of export agriculture, and use the reprieve gained from GATT to turn the sugar industry into a full-fledged chemical operation.